The Prevalence Of Metabolic Disorders And Their Associated Risk Factors In Forensic Patients With Schizophrenia Spectrum Disorders On Clozapine Compared To Haloperidol At Valkenberg Hospital - Mungly, Shazia (Department of Psychiatry and Mental Health, 2020)
Background: Various studies have shown that people with serious mental illness have an increased risk for metabolic syndrome with prevalence ranging from 28.7% to 60%. Given the amount of evidence suggesting a link between clozapine and metabolic syndrome, several guidelines have recommended regular clinical monitoring of metabolic syndrome in patients on clozapine. Aim: To determine the screening, prevalence and associated risk factors of metabolic disorders in forensic patients with schizophrenia spectrum disorders who are on clozapine (study group) compared to patients on haloperidol (control group). Methods: It is a retrospective, folder review of forensic male adult patients at Valkenberg Hospital, Observatory Cape Town. Results: There were 45 patients in the study group and 23 patients in the control group. Eight patients (17.8%) in the study group (Clozapine) met criteria for metabolic syndrome according to the NCEP-ATP III criteria and none of the patients in the control group (Haloperidol) did (χ 2 (1) = 4.441, p = .035 V = .257). Patients who had a diagnosis of schizoaffective disorder were also on mood stabilisers in addition to clozapine. Again, while none of the patients on Haloperidol met the criteria for Metabolic syndrome, 6 (24%) of the 25 patients on concurrent Clozapine and sodium valproate did, (χ 2 (1) = 6.051, p = .023 V = .359). In terms of metabolic disorders, a significantly higher proportion of patients in the study group has hypertension and hyperlipidaemia (p = .003 and p = .021 respectively). Less than 25% of all patients were fully screened for metabolic syndrome. There was a very low rate of screening of blood tests: fasting glucose, total cholesterol, trigylcerides, High Density Lipoprotein(HDL) or Low-Density Lipoprotein (LDL). Conclusion: The prevalence of metabolic syndrome was higher in the clozapine group than haloperidol group, which is unsurprising since clozapine is usually associated with a higher risk of metabolic syndrome. However, the prevalence on metabolic syndrome in this study sample was relatively low compared to other studies. This could be due to the low rate of screening of each criteria of metabolic syndrome. Screening for metabolic syndrome should be regularly performed by health professionals in patients with serious mental illness. Further studies are needed to investigate the risk of metabolic syndrome for patients who are on a combination of clozapine and mood stabilisers.